2002
DOI: 10.1179/026708301225000725
|View full text |Cite
|
Sign up to set email alerts
|

Very strong low temperature bainite

Abstract: Bainite has been obtained by heat treatment at temperatures as low as 125°C in a high carbon, high silicon steel. This has had the effect of greatly re® ning the microstructure, which is found to have a strength in excess of 2 . 5 GPa together with an ability to¯ow plastically before fracture. Such properties have never before been achieved with bainite. In this paper metallographi c details are reported of the very ® ne bainitic microstructure associated with the incredibly low transformatio n temperature, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
272
2
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 489 publications
(330 citation statements)
references
References 7 publications
9
272
2
6
Order By: Relevance
“…An unconventional, carbide-free steel has recently been invented which on close examination is found to contain bainitic-ferrite plates as thin as 20 nm, separated by carbon-enriched films of retained austenite [4,[19][20][21][22][23]. This is the hardest ever bainite, which can be manufactured in bulk form, without the need for rapid heat treatment or mechanical processing.…”
Section: Nanostructured Bainitementioning
confidence: 99%
“…An unconventional, carbide-free steel has recently been invented which on close examination is found to contain bainitic-ferrite plates as thin as 20 nm, separated by carbon-enriched films of retained austenite [4,[19][20][21][22][23]. This is the hardest ever bainite, which can be manufactured in bulk form, without the need for rapid heat treatment or mechanical processing.…”
Section: Nanostructured Bainitementioning
confidence: 99%
“…[10,11] Previous work has shown that these steels are relatively resilient to tempering. [1,8,12] The fine plate size provides the dominant strength contribution, so high hardness is maintained until coarsening of the bainitic ferrite occurs. [12,13] Development of alloys with increased temperature stability is in progress; this will rely on further suppressing carbide precipitation to increase the stability of the nanostructure.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Isothermal transformation circa 473 K (200°C) then results in a structure of fine bainitic ferrite plates (width 20 to 40 nm) separated by thin-films of austenite. [1,2,5] The fine scale of the structure is a consequence of the displacive transformation mechanism [6] and contributes significantly to the strength and hardness, [7] while retained austenite contributes to the toughness and elongation. [8] Carbide precipitation in a nanobainitic steel has been observed using atom probe tomography to be associated with the formation of carbon-depleted austenite after isothermal transformation at 473 K (200°C) in composition Fe-0.79C-1.5Si-1.98Mn-0.24Mo-1.06Al-1.59Co wt pct.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations